Investigation of factors affecting flame stabilization in meso-scale combustor - Muazzam Zainudin, Muhammad Ikhwan (2021)
Dwindling energy resources and strong demand for better power sources have sparked research interest in micro power generation. The invention of state-of-the-art electronic devices requires characteristics of which conventional batteries lack. Meso and micro combustors can be considered as the most important component in micro power generation. However, stabilizing a flame inside a meso combustor poses a great challenge to researchers. This difficulty is mainly related to the substantial heat losses due to large surface area to volume ratio. This research focuses mainly on the determining factors that affect the flame stabilization in meso-scale tube cylindrical tube combustors with stainless steel wire mesh. Apart from that, the combustion characteristics are also analyzed to establish the correlation between these factors that have significant effect on combustion. A three-dimensional (3-D) simulation model of combustor with stainless steel wire mesh was developed to numerically investigate the vital factors that contribute to flame stabilization by using ANSYS-Fluent software. The effective role of wire mesh in distributing heat from the burned to the unburned gas region was also demonstrated by using the developed 3-D simulation model. For the baseline model, the inner diameter of base three-dimensional (3-D) model is set at 3.5 mm while the outer wall thickness is 0.7 mm. Meanwhile, the stainless-steel wire mesh is modeled and placed between the unburned and burned gas region. The total length of the model is set to 40.2 mm. Propane (C3H8)-air mixture with equivalence ratio of 1.0 is used as the fuel source. The investigative factors that have been examined are the combustor geometry configuration such as the inner diameter and outer wall thickness, the wire mesh function and type of fuels. The results show that as the outer wall thickness increases from 0.3 mm to 1.5 mm, the blowout limits increase from 0.4 m/s to 0.5 m/s. As the wall thickness is above 1.5 mm, the blowout limit remains unchanged. On the other hand, there is insignificant increases of the blowout limit, which is from 0.47 m/s to 0.49 m/s with the use of thicker wire mesh from 0.4 mm to 0.8 mm. Apart from that, the use of combustor tube material with high wall thermal conductivity (k) significantly increases the blowout limit. Nevertheless, higher values of k beyond 100 W/mK is no longer effective for flame stabilization. The utilization of double wire mesh increases the blowout limits of from 0.47 m/s to 0.51 m/s. It is also shown that the stainless-steel wire mesh has a dual role function. At low flow velocity, the wire mesh tends to act as a flame inhibitor where heat is being transferred to the ambient. However, at higher flow velocities, the wire mesh acts as a flame enhancer where it circulates the heat into the unburned region. All these findings are important for future improvement of the proposed meso-scale combustor with wire mesh.